QUANTIFICATION OF IMMUNOGLOBULIN-A IN CHORIOAMNIOTIC MEMBRANE OF PATIENTS WITH PREMATURE RUPTURE OF MEMBRANES - Berezoswski, A. T.; Cunha, S. P.; Dacosta, J. C.; Bacchi, C. E. (Elsevier B.V., 1994)
Objective: the proposal was to study the presence of immunoglobulin A (IgA) in the chorioamniotic membrane of healthy postpartum women with premature rupture of the chorioamniotic membrane (FROM). Method: A single radial immunodiffusion technique was used to quantify the IgA in the chorioamniotic membrane tissues. Results: the level of IgA was approximately 10 times higher in patients whose membranes had been ruptured for > 10 h (24.58 mg/dl). These results were compared with those of a previously published study where the mean of amount of IgA was 2.52 mg/dl in membranes of patients with rupture < 10 h. Our results show that IgA began to rise after 10-15 h following rupture. Conclusion: Although more studies need to be performed our data indicate that the increasing IgA in our patients after 10 h of latency probably represents the beginning of an ascending colonization of bacteria which could be the source of future infection.
Keywords: IMMUNOGLOBULIN A; FROM; MEMBRANE RUPTURE; CHORIOAMNIOTIC MEMBRANE